Implementation of International Law Principles in Indonesian National Law - Budi Prasetyo; Jaden Tan; Rachel Chan (Yayasan Adra Karima Hubbi, 2025)
Background. The integration of international law principles into domestic legal systems is a complex and often contentious process. In Indonesia, the implementation of international law principles in national law involves balancing domestic legal norms with the obligations arising from international treaties and conventions. Objective. This study aims to examine how international law principles are implemented in Indonesian national law, focusing on the mechanisms, challenges, and effectiveness of their integration. The research seeks to identify key areas where international law is applied or disregarded in Indonesian legal practice and to provide recommendations for improving alignment with international standards. Method. A qualitative research approach was used, combining legal document analysis, case studies, and interviews with legal scholars, policymakers, and practitioners. This allowed for a comprehensive assessment of the practical application of international law principles in Indonesia’s legal system. Results. The study found that while Indonesia incorporates international law principles in specific areas, such as human rights and environmental law, there is often resistance or inconsistency in their implementation, particularly in areas that conflict with national interests. Conclusion. To enhance the effectiveness of implementing international law principles, this study recommends greater institutional cooperation, clearer legal frameworks, and the establishment of stronger enforcement mechanisms.